PERBAIKAN KUALITAS PRODUK TAHU BANDUNG DI TAHU NR MENGGUNAKAN METODE SEVEN TOOLS DAN HEART - Egar Naufal Ari Satya; Wahyudin Wahyudin; Rianita Puspa Sari (Universitas Katolik Parahyangan, 2022)
Tahu NR is a small factory that produces tofu Bandung, where the problems that often occur in Tahu NR are problems quality product tahu bandung like texture, dirty, and color defects. Because of these problems, it is necessary to control the quality of tofu Bandung products. The purpose of this study is to find out what factors cause defects in tofu Bandung products and identify activities that have a probability of error to workers in the production process of tofu Bandung as a basis for providing suggestions for improvements with the seven tools and the HEART method. The results of this study indicate that the factors that influence the defects of Bandung tofu products are human, machine, method, material, and environmental factors. The human factor is the most dominant factor because almost the entire production process is done manually, the number of workers is small with a large number of requests, and the frequent change of workers. All activities in the production process have a probability of error, this is because almost the entire production process in Tahu NR is done manually by workers. The greatest probability of error is in the printing process which has a potential error in the imperfect tofu printing process which can cause the tofu product to have defects in the texture with a HEP value of 0.311.